Challenges of Implementing the Federal Character Principles for National Unity in Nigeria / AbdulRasheed Hamza Bamidele, Raji Shittu and Amin Amin - Hamza Bamidele, AbdulRasheed; Shittu, Raji; Amin, Amin (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
The federal character principle was adopted in Nigeria to promote unity in diversity and ensure equitable development in all the geo-political zones of the country within the range of socio-political and economic equity. However, the implementation of the federal character policies, especially at the federal level of governance has been criticized for favoring the Northern part of Nigeria against the other parts of the country. The objective of this paper was to examine the implications of the federal character principle for socio-economy equity and political stability in Nigeria. Findings from the study, which relied on secondary sources as its method of inquiry, were that the federal character principle was designed to create fairness, justice, and equity among different geo-political zones in Nigeria and reduce the fear of sectional domination. The policy has enthroned some measure of fairness, justice, and equity in public policies in Nigeria, including those related to employment opportunities, promotion in public service, geographical representation, and quota admission policies in federal educational higher institutions. However, the federal character policy is still bedeviled by nepotism and sectional interest in Nigeria.